Missed opportunities in the treatment of Turner syndrome: a case discussion and review of the guidelines. Issue 8 (17th August 2022) - Howarth, Sophie; Quinton, Richard
Abstract : A woman in her 50s with Turner syndrome was referred to the endocrine clinic, having been unaware of her diagnosis until she received a shielding letter from the UK government during the COVID-19 pandemic. Despite a neonatal diagnosis of Turner syndrome on her general practitioner record and despite having undergone laparoscopic examination for absent puberty and primary amenorrhoea aged 18 years, she had not received any prior hormone treatment or cardiovascular screening. Though Turner syndrome is rare, recent data from the UK Biobank suggest that it may be underdiagnosed. Clinicians should be aware of the clinical features and associated complications of Turner syndrome to avoid delayed diagnosis and missed opportunities for treatment. In this report, we discuss the clinical features of this rare syndrome and current guidelines for screening and treatment. We stress the importance of peer-to-peer support and information sharing through patient-led groups, such as the Turner Syndrome Support Society.